Hubungan Dukungan Keluarga, Kecemasan Dan Peran Bidan Terhadap Kesiapan Ibu Dalam Menghadapi Persalinan Di PMB R Desa Sebagin Kecamatan Simpang Rimba : The Relationship between Family Support, Anxiety and the Role of Midwives on Mother's Readiness in Facing Childbirth in PMB R Sebagin Village, Simpang Rimba District - Arisandi, Deasy (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: Readiness is a level or condition that must be achieved in the process of individual development at the level of mental, physical, social, and emotional growth. The aim is to find out the relationship between family support, anxiety levels, and the role of midwives on mother's readiness to face childbirth at PMB Desa Sebagin, Kecamatan Simpang Rimba in 2022.  Methods: Analytical descriptive research using quantitative methods with a cross-sectional approach. The population is pregnant women using total sampling and the number of samples used is 45 people.  Results: The results of the analysis found a p-value = 0,038; which means that there is no family support for the mother's readiness to face childbirth. The results of the statistical test obtained a p-value = 0,006; which means that there is a relationship between the anxiety variable between the readiness of the mother to face childbirth. The results of the statistical test obtained a p-value = 0,012; which means that there is a relationship between the role of the midwife and the readiness of the mother to face childbirth.  Discussion: The conclusion is that there is a relationship between family support, anxiety, and the role of midwives in the readiness of mothers to deal with childbirth at PMB R, Desa Sebagin, Kecamatan Simpang Rimba in 2022. It is expected that pregnant women routinely check their pregnancies with health workers so they can find out their HIV status earlier and carry out HIV/AIDS prevention behaviors.